Next-Generation Sequencing of Circulating Tumor DNA Can Optimize Second-Line Treatment in RAS Wild-Type Metastatic Colorectal Cancer after Progression on anti-EGFR Therapy: Time to Rethink Our Approach - Mauri, Davide; Kamposioras, Konstantinos; Matthaios, Dimitrios; Tolia, Maria; Nixon, Ioanna; Dambrosio, Mario; Zarkavelis, Georgios; Papadimitriou, Konstantinos; Petricevic, Branka; Kountourakis, Pantelis; Kopecky, Jindrich; Grašič Kuhar, Cvetka; et al. (Oncology research and treatment, 2022)
BACKGROUND: Management of Ras wild-type colorectal cancer (CRC) patients upon disease progression after the successful use of targeted treatment with anti-EGFR monoclonal antibodies and backbone chemotherapy remains a clinical challenge. SUMMARY: Development of treatment resistance with prevalence of preexisting RAS mutated clones, RAS mutation conversion, truncation of extracellular receptor domains as well as HER2 and MET amplification are molecular events that can be difficult to follow without the use of sophisticated laboratory techniques. The clinical hurdle of re-biopsy and tumor heterogeneity can be overcome by the implementation of next-generation sequencing (NGS) to analyze circulating tumor DNA (ctDNA) and identify druggable mutations or recovery of RAS-wildness. In this opinion paper, we summarize with critical thinking the clinical approach to be followed after the failure of first-line treatment in Ras wild-type CRC tumors with the use of NGS. Rechallenge with anti-EGFR inhibitors, in case of persistent or recovery of RAS-wildness, and targeted approach of specific mutations (BRAF inhibitors), amplifications (anti-Her2 treatment), or fusion proteins (NTRK inhibitors) can by guided by the use of NGS. The use of NGS platforms for serial analysis of ctDNA is an important step to better understand the molecular landscape of metastatic CRC and guide clinical decisions. KEY MESSAGES: NGS should be considered a mainstay in clinical practice for the management of CRC patients and health authorities should consider reimbursing its use in the appropriate clinical settings.
Keywords: cirkulující nádorová DNA; Mutation; vysoce účinné nukleotidové sekvenování; kolorektální nádory; Circulating Tumor DNA; Oncogenes; High-Throughput Nucleotide Sequencing; Colonic Neoplasms; lidé; Humans; mutace; Colorectal Neoplasms; onkogeny; nádory tračníku